Chalcogen bonding interactions in chelating, chiral bis(selenocyanates). (8th December 2020) - Huynh, Huu-Tri; Jeannin, Olivier; Aubert, Emmanuel; Espinosa, Enrique; Fourmigué, Marc
Abstract : Both anti (racemic mixture) and syn ( meso ) forms of a chiral, chelating chalcogen bond (ChB) donor interact with halides through short Se⋯X − directional interactions. Abstract : Introduction of methyl substituents on the achiral 1, 2-bis(selenocyanatomethyl)benzene leads to a novel chelating ChB donor, namely 1, 2-bis(1-selenocyanatoethyl)benzene (1 ), as a mixture of three diastereomers, the two anti enantiomers and the syn ( meso ) form. Structure determinations show the recurrent formation of short Se⋯NC ChB interactions in both the anti (racemic mixture) and syn isomers. Co-crystallization of anti -1 with 4, 4′-bipyridine affords a 2 : 1 adduct, ( anti -1 )2 (bipy), with one very short Se⋯NPy ChB (RR = 0.87). Co-crystallization of anti -1 with tetraphenylphosphonium halides (Cl −, Br −, I − ) provides 1 : 1 adducts while a 2 : 1 adduct is isolated between syn -1 and Et4 NCl, formulated as Et4 N + [( syn -1 )2 Cl − ]. Comparison of chloride chelation with anti -1 and syn -1 shows much shorter (NC)Se⋯Cl − ChB interactions with the syn isomer, tentatively rationalized on the basis of theoretical calculations of (i) the electrostatic surface potential of neutral ChB donors and (ii) the chloride BSSE complexation energy.